Consumer preferences for different designs of carbon footprint labeling on tomatoes in Germany - Does design matter? - Stephan G. H. Meyerding and Anna-Lena Schaffmann and Mira Lehberger (Sustainability, 2019)
The climate impact of tomato production is an important issue in the sustainability of tomatoes, especially in northern European countries, such as Germany. Communicating the climate impact of products to the consumer is difficult and the design of the label might be the key to its success. For this reason, the present study compares the utilities of six different carbon footprint labels to evaluate which label design works best for the consumer. 598 consumers were surveyed in a representative online choice-experiment. The participants had to choose between tomatoes with different product characteristics, such as origin, price, organic label, and carbon footprint label. A split sample approach was used where each sub-sample with around n = 100 saw a different carbon footprint label design in the choice-experiment. The results suggest that qualitative carbon footprint labels using color-coded traffic light labelling are superior to those that claim climate impact reduction or neutrality, including those that provide more details regarding the climate impact of the product and the company. The latent class analysis with four consumer segments shows that a significant proportion of consumers in Germany would consider a carbon footprint label as an important characteristic.
Keywords: Choice-based con-joint analysis; Consumer preferences; Latent class analysis; Marketing; Product carbon footprint label